2011
DOI: 10.1007/s13337-011-0048-x
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Virus like Particles in Human Pathogenic Fungi: Chrysosporium sps and Candida albicans

Abstract: Out of eight isolates of different human pathogenic fungi, four were found to be infected with virus like particles (VLP): Chrysosporium pseudomerdarium, C. xerophillum, C. keratinophillum and Candida albicans through electron microscopy. Frozen mycelium without abrasive was seemingly better disruption method for VLP extraction in Chrysosporium extracts but in Candida albicans disruption with abrasive revealed the presence of considerable amount of VLP. The growth of five isolates of Chrysosporium species asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Recent studies showed an increased burden of M. restricta on the scalp of patients with dandruff, indicating an association between dandruff and the fungus, although its role as a pathogenic organism is still unclear, and host susceptibility should be taken into consideration ( 21 , 24 27 ). Most fungal viruses are found in plant-pathogenic fungi, whereas few examples of viral particles have been identified in human-pathogenic fungi such as Candida albicans ( 28 ). In the present study, we observed extrachromosomal dsRNA segments in various M. restricta clinical isolates which represented a novel viral genome and its satellite.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed an increased burden of M. restricta on the scalp of patients with dandruff, indicating an association between dandruff and the fungus, although its role as a pathogenic organism is still unclear, and host susceptibility should be taken into consideration ( 21 , 24 27 ). Most fungal viruses are found in plant-pathogenic fungi, whereas few examples of viral particles have been identified in human-pathogenic fungi such as Candida albicans ( 28 ). In the present study, we observed extrachromosomal dsRNA segments in various M. restricta clinical isolates which represented a novel viral genome and its satellite.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, double-stranded RNA virus has been identified in the human pathogenic fungus Blastomyces dermatitidis (Kohno et al, 1994 ). A recent study using electron microscopy demonstrated that several human pathogenic fungi were infected by virus-like particles (Sharma et al, 2011 ). However, to our knowledge, no study has clearly identified a virus in the human pathogenic fungus so far.…”
Section: Discussionmentioning
confidence: 99%
“…Although not as prevalent as bacteriophages, mycophages might represent a treatment option for fungal infections [ 176 ]. Despite not being studied as much as bacteriophages, mycophages have been studied predominantly in Aspergillus [ 177 ], but have also been reported in Candida [ 178 ]. It has been shown that some mycophages can be transferred from Aspergillus to Saccharomyces [ 179 ], demonstrating that mycophages can have a broad host range.…”
Section: Non-traditional Antifungal Optionsmentioning
confidence: 99%